β-Secretase 1’s Targeting Reduces Hyperphosphorilated Tau, Implying Autophagy Actors in 3xTg-AD Mice - Piedrahita, Diego; Castro-Alvarez, John Fredy; Boudreau, Ryan L.; Villegas-Lanau, Andres; Kosik, Kenneth S.; Gallego-Gomez, Juan Carlos; Cardona-Gómez, Gloria Patricia (Frontiers in Cellular Neuroscience, 2016)
β-site APP cleaving enzyme 1 (BACE1) initiates APP cleavage, which has been reported to be an inducer of tau pathology by altering proteasome functions in Alzheimer’s disease (AD). However, the exact relationship between BACE1 and PHF (Paired Helical Filaments) formation is not clear. In this study, we confirm that BACE1 and Hsc70 are upregulated in the brains of AD patients, and we demonstrate that both proteins show enhanced expression in lipid rafts from AD-affected triple transgenic mouse brains. BACE1 targeting increased Hsc70 levels in the membrane and cytoplasm fractions and downregulated Hsp90 and CHIP in the nucleus in the hippocampi of 3xTg-AD mice. However, these observations occurred in a proteasome-independent manner in vitro. The BACE1miR-induced reduction of soluble hyperphosphorylated tau was associated with a decrease in MAPK activity. However, the BACE1 RNAi-mediated reduction of hyperphosphorylated tau was only blocked by 3-MA (3-methyladenine) in vitro, and it resulted in the increase of Hsc70 and LAMP2 in lipid rafts from hippocampi of 3xTg-AD mice, and upregulation of survival and homeostasis signaling. In summary, our findings suggest that BACE1 silencing neuroprotects reducing soluble hyperphosphorylated tau, modulating certain autophagy-related proteins in aged 3xTg-AD mice.